RESPONS KETAHANAN LIMA VARIETAS CABAI MERAH (Capsicum annum L.) TERHADAP BERBAGAI KONSENTRASI GARAM NaCl MELALUI UJI PERKECAMBAHAN - Didik Triadi; T. Chairun Nisa; Sanggam Silitonga (Jurnal Agroekoteknologi, 2013)
The aim of the research was to find out resistance of the five varieties of chili pepperto various concentrations of NaCl salt by Germination Test. The research wasconducted in the seed technology laboratory of the Faculty of Agriculture, Universityof North Sumatera on December 2011. The research used Randomized Block Designwith two factors and three replication. The first factor was variety, consisting of fivevarieties, namely Laris, Mario, TM 007, TM 999, and Hot Star. The second factor wassalt concentration, consisting 4 levels, namely G0(0 ppm), G1 (1000 ppm), G2 (2000ppm), and G3 (3000 ppm). The parameters observed in this research were germinationpercentage, germination rate, percentage of normal and abnormal seedlings,percentage of dead seeds, seedling fresh weight and seedling height. The resultsshowed that varieties significantly effected germination rate, percentage of deadseeds, seedling fresh weight and seedling height. While salt concentration did notshow any significant affect on all parameters. It can be concluded that among thevarieties tested, the Mario variety showed best tolerance to NaCl salt, the leasttolerance was Hot Star.Keywords : red chili, variety, NaCl, germination